Book Review: Not either an experimental doll (1987): edited by Shula Marks - Letlaka-Rennen, Kedibone (PINS-Psychology in Society, 2025)
The country is South Africa, the year 1948. In response to an impassioned letter from a deprived Xhosa girl (Lily Moya), pleading for assistance with furthering her education, Dr Mabel Palmer an educationist known for her substantial contribution to and interest in black education in Natal, and earlier work with feminist issues eventually arranges and pays for Lily's travel, board, plus schooling at Adams College - (a leading black school in Natal). Having attempted the matriculation examination in less than optimal conditions at Saint John's College in Umtata, Transkei and failed to gain university entrance, Lily was convinced that given a different set of circumstances she could do better. Her written appeal charmed and enthused Mabel Palmer sufficiently to afford her that second opportunity. At a superficial first glance this scenario all looks humane, touching and straightforward enough.